Pandangan Hukum Syara' (Hukum Islam) terhadap Hisab Ru'yah - Rusdin Muhalling (Institut Agama Islam Negeri (IAIN) Kendari, 2009)
This article is a study with Science study of Hisab and of Ru’yah, utilized by Islam people in practice religious service one day, religious service especially of salat, fasting religious service, and religious service of Haji. With fundamental salution of execution of the science in determining early time of salat, instruct Qiblat, and early month; moon of Qamariyah precisely and research. Thereby, the writer tells in this article, ad for theoretically and practice of, how the ability of this science in determining the early time of salat, instruct Qiblat, and early month; moon of Qamariyah at one particular place. Truth and correctness of can be proved pursuant to the formula specified by pertinent science. Especially early time of salat, instruct Qiblat, and determination early month; moon of Ramadhan and early month; moon of Syawal, for the feast day of Ramadhan of Idul Fitri, the result of Ru’Yah and Hisab earn proved and justified scientifically.